GAMBARAN KUALITAS FISIK UDARA DAN KELUHAN SUBJEKTIF PADA PEKERJA BAGIAN PRODUKSI PT PAGILARAN UNIT PRODUKSI JATILAWANG TAHUN 2021 - Joko Malis Sunarno; Meylinda Endah Sari (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2022)
Physical work environment affect the results of the work. Therefore, it is necessary to design the physical working environment for worker comfort and avoid subjective complaints in workers. The purpose of this research is to know the description of the physical quality of the air and subjective complaints on the workers part of the production of PT Pagilaran Production Unit Jatilawang. This research includes descriptive research method with cross secsional. The population in this research is all of the workers in the production section. The sampling technique using total sampling. The Data used in this research is primary data obtained from the measurement of the physical quality (lighting,noise,temperature) and interviews with a questionnaire subjective complaints. Workers will each have 30 questions. The results of measurements of the physical environment states that the intensity of the lighting is not eligible, the intensity of the noise is eligible, and the intensity of the temperature eligible. Subjective complaints of the average worker no experience or don't complain (>90%). There are only 3 workers had complaints from the intensity of the lighting, 2 workers have complaints of noise intensity and 1 workers have complaints from the intensity of the temperature in the work environment. PT Pagilaran Production Unit Jatilawang expected to add artificial lighting.